2020
DOI: 10.3390/ijerph17239042
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Long Exercise Program in the Reduction of Musculoskeletal Discomfort in Office Workers

Abstract: The purpose of this study was to assess the effect of a six week exercise program to reduce the muscle tone of the trapezius and musculoskeletal discomfort (MED) of office workers. Twenty-six workers performed an exercise program based on: (1) stretching of cervical and/or dorsal region; (2) joint mobility of shoulders and rachis; (3) strengthening deep stabilizer and core muscles; and (4) scapula stabilizing exercises. A Myoton device was used to evaluate trapezius tone and the Cornell Musculoskeletal Discomf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 40 publications
(50 reference statements)
0
10
0
1
Order By: Relevance
“…Secondly, the assumptions for health and wellness benefits were generally concordant with the literature. For instance, multiple studies have tested the effects of stretching programs implemented in office settings [ 44 , 45 , 46 , 47 ]. These studies were generally conclusive for significantly improved health-related quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, the assumptions for health and wellness benefits were generally concordant with the literature. For instance, multiple studies have tested the effects of stretching programs implemented in office settings [ 44 , 45 , 46 , 47 ]. These studies were generally conclusive for significantly improved health-related quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, it was reported that physical exercise can control the risk factors of fatigue [28,29] and MSDs [30][31][32][33][34][35][36][37][38][39][40]. The types of physical exercise used were physical exercise [30], stretching [31,32], resistance training [28,33], strength training [34], and a combination of stretching and games [30].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a combination of stretching, resistance, and strength training provides the best results [33,41]. Physical exercise has various durations and the frequency of intervention times varies: resistance exercises once a day for 20 min, three times a week for 4 months [28]; 1-h low-intensity running sessions three times a week for a period of six consecutive weeks [29]; 36 different stretches once every 6 min, with stretches lasting 10 to 15 s for 15-17 workdays [31]; a worksite-based physical activities program once a day, lasting 10 min, for 12 months [35]; 10 min daily exercise session for 2 months [36]; physical exercise for 20 min, three times a week for 12 months [37]; resistance training lasting 2 and 12 min, five times a week for 10 weeks [33]; three strength training interventions with different frequencies and durations (1 h once a week, 20 min three times a week, and 7 min nine times a week) for 2 weeks [34]; stretching two times/week for 5-15 min, lasting 6 weeks [38]; exercise training for 10-15 min, three times a week for 11 weeks [39]; exercise two times a week for 3 months [30]; and stretching exercises lasting 10-15 min, two times a day for 4 weeks [32].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stretching has long been a common modality before and after training during different exercise stages [18]. The efficacy of stretching as an aid to performance is less apparent; however, the benefit may lie in the alleviation of discomfort and pain [16,19]. Particularly, chronic stretching may reduce injury [18].…”
Section: Introductionmentioning
confidence: 99%